Comparing Likert and Q: The potential of Q methodology to study pre-service teachers’ beliefs of teaching and learning of mathematics - Buchholtz, Nils; Vollstedt, Maike (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
Different methods are used to study pre-service teachers’ beliefs of teaching and learning mathematics. A common way is using Likert scale surveys to measure agreement or disagreement on items. In Q methodology, participants are asked to relate statements by ordering them in a Q-sort grid and explicate their sort. Then, the sorts of all participants are statistically analysed to detect different types of sorts (factors). In our study, N = 25 pre-service teachers filled out a Likert scale survey and then related the same items in a Q-sort. Our aim is to compare the scope of the two approaches to work out the specific insights of Q. Results from the Likert scale analyses show that pre-service teachers primarily hold constructivist views. In addition, the Q-analysis reveals typical sorts of a certain group of pre-service teachers. They can be described with respect to their subjective view based on distinguishing statements.